What I missed from my online therapist: A survey-based qualitative investigation of patient experiences of therapist contact in guided internet interventions - Sayar, Hanna; Vøllestad, Jon; Nordgreen, Tine (Frontiers in Psychology, 2023)
Background The effectiveness of internet-delivered cognitive behavioral therapy (ICBT) in alleviating symptoms of psychological disorders has been demonstrated across qualitative and quantitative studies. Generally, guided ICBT is considered more effective than unguided ICBT. Yet, what therapist contact and guidance specifically add to the treatment is less clear. There is a need for more knowledge about how patients experience the relationship with their therapist in guided ICBT. The aim of the study was to explore what patients missed in the contact with their therapist in guided ICBT in routine care. Methods The study used a qualitative design to explore patients´ experiences of the therapist contact in guided ICBT for social anxiety disorder, panic disorder or major depressive disorder. Following treatment, 579 patients received a survey with the open-ended question “What did you miss in the contact with your therapist?” The responses were explored thematically using qualitative content analysis. Results A total of 608 unique responses were provided. Of these, 219 responses gave voice to some degree of perceived lack or limitation in their interaction with the therapist or the treatment in general. The analysis yielded three main categories: The first theme, Therapist-ascribed shortcomings, concerned experiences of something missing or lacking in the contact with the ICBT therapist. More specifically, the patients expressed a need for more emotionally attuned and tailored interaction. The second theme was Program obstacles, encompassing expressed wishes for increased therapist responsivity and more contact face-to-face. Self-attributed limitations, the third category, concerned patient experiences of barriers to treatment engagement as originating in themselves. Conclusion This study sheds light on what patients in routine care missed in the contact with their therapist. The patients who expressed that something was missing in the contact with their therapist constituted a small part of the responses in the sample, even after being directly asked. The themes that emerged point to significant experiences of being inadequately related and responded to, both with potential adverse consequences for the treatment. These findings give new insights to the role of the guidance in ICBT and have implications for the training and supervision of guided ICBT therapists.